The effect of 6-week zinc supplement and weight training on the blood lipids of the sedentaries and athletes - Cinar, Vedat; Akbulut, Taner; Kilic, Yakup; Ozdal, Mustafa; Sarikaya, Mucahit (C M B Assoc, 2018)
In this study, we aimed to investigate the effect of 6 weeks of zinc supplementation and weight training on blood lipids of sedentary and athletes. Research group consists of total 40 males; 20 athletes who do regularly physical exercises and 20 sedentary volunteers. The volunteers were divided into four groups. These groups were constituted in that way: the first group is a natural sedentary group which called control group as well (S); the second group is another sedentary group which is supplied with only zinc (Z+S); the third group is training group which composing of athletes and is supplied with zinc (Z+T); the fourth group is the natural training group or athletes (T). From the beginning of the study to the end of 6-weeks of training, the participants gave blood samples before and after every application order to measure the total cholesterol, LDL cholesterol and HDL cholesterol and the levels of Triglyceride. This study identifies that the values of the total cholesterol, LDL cholesterol and Triglyceride of the groups which were supplied with zinc supplement decreased, whereas the levels of HDL cholesterol increased in these groups. Consequently, this work demonstrates that the 6-weeks zinc supplement and training can make a significant contribution to the performance by changing positively the levels of blood lipid.
Keywords: Training; Lipid; Zinc supplement; Cholesterol; Sedentary